Integration of a side-stream microalgae process into a municipal wastewater treatment plant: A life cycle analysis. (1st February 2021) - Tua, Camilla; Ficara, Elena; Mezzanotte, Valeria; Rigamonti, Lucia
Abstract: This study investigates the environmental improvements associated to the integration of a microalgae unit as a side-stream process within an existing municipal wastewater treatment facility in northern Italy. Microalgae are fed on the centrate from sludge dewatering, rich in nutrients, and on the CO2 in the flue-gas of the combined heat and power unit. The produced biomass is recirculated upflow the water line where it settles and undergoes anaerobic digestion generating extra biogas. A life cycle assessment was performed collecting primary data from an algal pilot-scale plant installed at the facility. Fifteen environmental indicators were evaluated. Compared to the baseline wastewater treatment, the new algal configuration allows an improvement for 7 out of 15 indicators mainly thanks to the electricity savings in the facility. Some recommendations are provided to improve the performance of the algal system in the scaling up. Highlights: A life cycle assessment of a WWT with a side-stream microalgae unit was performed. Environmental improvement in 7 out of 15 indicators compared to the baseline WWT. NH3 stripping (0.6 g/m 3 influent wastewater) is one of the main impact contributors. More than 45% of the human toxicity impact is due to undigested biomass treatment. Recommendations are given to make the algal system eco-friendlier in the scaling up.